A noise elimination procedure for wavelet-based printed circuit board inspection system - Ibrahim, Zuwairie; Al-Attas, Syed Abdul Rahman; Onot, Osamu; Mohd. Mokji, Musa (IEEE, 2004)
Image difference operation is fkequently used in automated printed circuit board (PCB) inspection system as well as in many other image processing applications. The previously proposed wavelet-based PCB inspection approach also incorporated the point-to-point image difference operation as part of its algorithm. Unfortunately, during the implementation, this operation brings along the unwanted noise due to misalignment and uneven binarization. Thus, this paper proposes a method to eliminate, if possible, or to reduce as much as possible such noise during the computation of defect detection. The results of applying the proposed method showed a significant improvement during the real-time inspection of printed circuit boards.